To Assess the Nutritional Status and Morbidity Pattern Of Children aged 6 Months to 5 Years belonging to Rural Area Of Abhanpur Block - Sharja Phuljhele; Pratima Beck; Devendra Kumar (Pediatric Review: International Journal of Pediatric Research, 2022)
Introduction: Malnutrition among children is India’s well-known social and public health problem.There is a similar situation in Chhattisgarh with 37% under-5 children underweight. About 700million people in India live in rural areas and have basic health facilities and poor environmentalconditions that make children susceptible to infectious diseases. Objective: To assess the nutritionalstatus and morbidity pattern in children aged 6-60months belonging to the rural area of abhanpurblock. Methods: Cross-sectional study was conducted in a rural area the Abhanpur block of theRaipur district. A sample of 360 children from January 2019 to December 2020 wasanthropometrically and clinically assessed for their nutritional status and their morbidity pattern.Socioeconomic variables were also collected to identify the determinants of nutritional status andmorbidity patterns. Where was analyzed using SPSS-20 and WHO-Anthroplus Informed consent andethical issues were considered. Results: Out of the 360 children, the mean age of sample childrenwas 2.73±1.16 years, 28.61% were in the 2-3 year age group and 51.39% were female. Themajority of them belong to low socioeconomic (78.33%) status. As per WHO nutritionalmeasurement criteria, 26.12% were underweight, 5.88% were severe wasting, and 9.44% in severestunting. Major morbidity conditions among study participants were respiratory infections (28.32%),diarrhea (18.21%), conjunctival-pallor (20%), scabies (21.51%), and 11.94% dental carries.Parental education, diarrhea/respiratory- infection, and the mother’s occupation were significantdeterminants for underweight study children. Conclusion: Almost every 4th the Children living inthe rural area are underweight and have many common morbidities which lead them into the viciouscycle of recurrent infections and malnutrition.